Influence of Combining Real-time and Fixed Tariffs in the Demand Response Aggregation and Remuneration Scheems Definition - Silva, Catia (2021)
The electric sector revolution towards Smart Grids, requires new market models. The authors propose a business model that allows the virtual power player to manage the small resources like distributed generation units, consumers belonging to demand response programs, and prosumers. Grouping these resources and remunerating them according to the maximum tariff of the group that was allocated is proposed. The purpose of this paper is to understand whether the tariff associated with each resource influences or not the formation of groups when applying the clustering method. Three case studies were carried out: aggregation only with the potential of each resource, power and the fixed tariff and, finally, taking into account a tariff that changes according to the period of the day.